Empirical Analysis of Household Energy Demand Using Almost Ideal Demand System: A Case Study of District Muzaffarabad, Azad Kashmir, Pakistan - Khan, Ghulam Yahya; Rashid, Syeda Nazish; Mehboob, Salik (Energy Economics Letters, 2018)
Energy provides input for keeping sustainability in economic growth. This research work is designed to investigate the household energy demand and to explore the factors that determine household energy demand for different forms of energy consumption in district Muzaffarabad of the state of Azad Jammu and Kashmir, Pakistan. By using Linear Approximate Almost Ideal Demand System (LA-AIDS), this study estimated Marshallian price and expenditure elasticities of demand for four kinds of energy components including both rural and urban households. Using primary data LA-AIDS estimation indicated that demand for all forms of energy are price inelastic. Cross price relations indicated that electricity is a substitute for LPG, wood and fuel whereas LPG and fuel are complements. Electricity has most inelastic own-price elasticity which shows that households in Muzaffarabad are insensitive to changes in the price of electricity.